(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
An induction that aims to trace the image of critics’ poetry in a chosen model, namely Al-Mazni, and extract the meters that he used as a critic and poet, and monitor the musical phenomena that were celebrated and distinguished by his poetry, as poetry is considered a category with a single system of culture and practice closely related to literary theory, as the study is based on clarifying The relationship between theory and practice, and was there a critical impact on its weights? What is the nature of his poetry in terms of weights? Did he criticize his poetry? What musical innovation did he bring? Did his poetry style differ from that of other poets, or did he follow the path of the poets who preceded him? From this standpoint, this research came to provide an integrated vision of Al-Mazni’s experience, primarily concerned with the musical aspect of his poetry.